EFFECT OF WOOD-LOAD WOOD-LOADING PROCEDURES (Manihot esculenta Crantz) ON PADI CONTENT AND QUALITY OF UVAN WOOD FLOUR - Wika Rinawati (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2003)
This research is about flouring procedures, which do with three ways.First (grating and drying). Second (grating, parting of starch and waster). Third (grating and drying of waster). Goals from this research are: 1) to know cassava's flour starch based on difference of flouring procedure 1, II, and 111,2) to know about impact of flouring procedure difference 1, 11, and 111on cassava's flour starch compared with fresh cassava, and 3) to know the impact of flouring procedure difference 1, 11 and 111on quality (colour and smell) cassava's flour. Research were did at Food Biochemical Laboratory Farm Technology Gadjah Mada University to analyze flour and Culinary Laboratory, Family Life Education, Technique Faculty, Yogyakarta State University, where flour product was made. Research start with make a starch with starching procedure 1, 11, and 111 and continued with analyzing cassava and sensoric test of cassava's flour quality which depend on colour and smell. The research show that: 1) cassava's flour starch in 1 way 86.69%, 11is87.94%, 111 is 87.I4%. 2) there is impact of flouring procedure on cassava's flour starch compared with fresh starch. There is no difference impact offlouring procedure 1, II, and IlIon cassava's starch flour at 1% significantly. 3) There is impact on flouring procedure difference on colour and smell cassava's flour at 1% significantly.